The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/rs12091470
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Estimating Crop Residue Cover from Sentinel-2 Data Using Empirical Regressions and Machine Learning Methods

Abstract: Quantifying crop residue cover (CRC) on field surfaces is important for monitoring the tillage intensity and promoting sustainable management. Remote-sensing-based techniques have proven practical for determining CRC, however, the methods used are primarily limited to empirical regression based on crop residue indices (CRIs). This study provides a systematic evaluation of empirical regressions and machine learning (ML) algorithms based on their ability to estimate CRC using Sentinel-2 Multispectral Instrument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In the past decade, the focus was mainly on the quantification of crop residue or NPV coverage (in %) from remote sensing data (e.g., [ 33 ]). Hereby, applied methods ranged from empirical algorithms (e.g., crop residue indices), over classification [ 34 ], to spectral unmixing [ 11 ], spectral angle methods [ 35 ] and spectral mixture analysis (SMA) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the focus was mainly on the quantification of crop residue or NPV coverage (in %) from remote sensing data (e.g., [ 33 ]). Hereby, applied methods ranged from empirical algorithms (e.g., crop residue indices), over classification [ 34 ], to spectral unmixing [ 11 ], spectral angle methods [ 35 ] and spectral mixture analysis (SMA) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Li et al (2014) showed that the larger the dataset, the better the performance of the random forest model in their study on improving the linkage affinity prediction of scoring functions on the substitution of random forest for linear regression. This conclusion was also reached by Ding et al (2020) in their study on the comparison of empirical regressions and machine learning methods for crop residue cover estimation using Sentinel-2 data, as well as by Wang et al (2016) in their study on wheat biomass estimation using the random forest regression algorithm and remote sensing data. They all reported that the accuracy of the machine learning approaches was improved when increasing the training sample size relative to the total sample population.…”
Section: Selection Of Modeling Approachmentioning
confidence: 78%
“…Recently, Beeson et al, (2020) used Landsat-derived NDTI to map conservation tillage in three Midwest states over a 10-year period, with overall accuracies ranging from 64% to 78%, which is a typical accuracy range for studies employing this index [4]. In addition to use of spectral indices for NPV cover estimation, researchers using broadband multispectral imagery have employed various innovative methods such as spectral unmixing (Laamrani et al, 2020; R 2 = 0.70 [29]) and machine learning (Ding et al, 2020; R 2 = 0.69 [30]), but seldom do such studies produce accuracies exceeding 80%.…”
Section: Crop Residue Measurement Using Broadband Multispectral Indicesmentioning
confidence: 99%